Unilateral or Bilateral Laparoscopic Ovarian Drilling in Polycystic Ovary Syndrome: A Meta-analysis of Randomized Trials - Faezeh Zakerinasab; Qumars Behfar; Taif Haitham Al Saraireh; Mahdyieh Naziri; Shirin Yaghoobpoor; Niloofar Deravi; Reza Khademi; Fariba Arbab Mojeni (Gynecology and Minimally Invasive Therapy)
Objectives: On the first line of polycystic ovary syndrome (PCOS) treatment, ovulation with clomiphene citrate (CC) is induced. However, 25% of patients need alternative therapy. Laparoscopic ovarian drilling (LOD) can result in successive ovulations and is not linked to ovarian hyperstimulation. In this systematic review and meta-analysis, we aimed to consider the efficacy of unilateral LOD (ULOD) versus bilateral LOD (BLOD) for enhancing fertility and improving fertility outcomes in women with CC-resistant. Materials and Methods: A comprehensive literature search was conducted up to July 15, 2023, to identify relevant randomized controlled trials in PubMed, Scopus, Google Scholar, and Cochrane Library databases. Thirteen articles were included in the meta-analysis. After data extraction, we performed a meta-analysis. Results: As the main unit of analysis for each variable, the standardized mean difference was used between the two groups. The random effects model was used for analysis and heterogeneity was assessed by I2 statistics. Publication bias was inspected through funnel plots and Begg’s and Egger’s regression tests. The included studies were divided into two general categories. In the first category, surgical treatment of LOD was compared with other treatments. Whereas, in the other category, ULOD was compared with BLOD. Conclusion: In summary, this meta-analysis did not find a significant difference in the rate of ovulation, pregnancy, miscarriage, and live birth between the two groups. However, LOD could cause damage to the ovarian reserve, but it has long-term effects on improving the menstrual cycle and reproduction. In general, LOD is a significant method for the treatment of infertility in PCOS, which needs further investigation.